Exploring the relationship between nutritional intake and menstrual cycle in elite female athletes - Miyamoto, M.; Shibuya, K. (PeerJ, 2023)
This study aimed to examine potential variations in nutritional intake among female athletes, including top-level, throughout the menstrual cycle. A total 122 female athletes participated in the study, documenting their food consumption over a 3-day period. The menstrual status of female athletes was also assessed, and using the survey results, the phase of the menstrual cycle (the follicular, early luteal, or late luteal) during which each meal was recorded was determined. Consequently, the meal records were categorized into the respective three phases. The findings of this study indicated that there were no notable disparities in nutritional intake, encompassing energy, protein, fat, carbohydrate, calcium, iron, and fiber, across the three phases of the menstrual cycle. The results imply that female athletes may experience comparatively smaller variations in nutrient intake related to the menstrual cycle. This could be attributed to the higher energy requirements of female athletes because of their rigorous training. This study underscores the significance of accounting for the population when examining nutrient intake changes associated with the menstrual cycle.